Data Science with Python : Combine Python with Machine Learning Principles to Discover Hidden Patterns in Raw Data. - Chopra, Rohan (Packt Publishing, Limited, 2019)
Data Science with Python will help you get comfortable with using the Python environment for data science. You will learn all the libraries that a data scientist uses on a daily basis. By the end of this course, you will be able to take a large raw dataset, clean it, manipulate it, and run machine learning algorithms to obtain results that ...